Problem:
 f(x,g(x)) -> x
 f(x,h(y)) -> f(h(x),y)

Proof:
 Complexity Transformation Processor:
  strict:
   f(x,g(x)) -> x
   f(x,h(y)) -> f(h(x),y)
  weak:
   
  Matrix Interpretation Processor:
   dimension: 1
   max_matrix:
    1
    interpretation:
     [h](x0) = x0 + 4,
     
     [f](x0, x1) = x0 + x1 + 12,
     
     [g](x0) = x0
    orientation:
     f(x,g(x)) = 2x + 12 >= x = x
     
     f(x,h(y)) = x + y + 16 >= x + y + 16 = f(h(x),y)
    problem:
     strict:
      f(x,h(y)) -> f(h(x),y)
     weak:
      f(x,g(x)) -> x
    Matrix Interpretation Processor:
     dimension: 2
     max_matrix:
      [1 1]
      [0 1]
      interpretation:
                      [0]
       [h](x0) = x0 + [1],
       
                     [1 0]     [1 1]     [2]
       [f](x0, x1) = [0 0]x0 + [0 1]x1 + [0],
       
                      [1]
       [g](x0) = x0 + [1]
      orientation:
                   [1 0]    [1 1]    [3]    [1 0]    [1 1]    [2]            
       f(x,h(y)) = [0 0]x + [0 1]y + [1] >= [0 0]x + [0 1]y + [0] = f(h(x),y)
       
                   [2 1]    [4]         
       f(x,g(x)) = [0 1]x + [1] >= x = x
      problem:
       strict:
        
       weak:
        f(x,h(y)) -> f(h(x),y)
        f(x,g(x)) -> x
      Qed